Effective Methods for Organizing Intensive Gardens and Maximizing Income (Texas Journal of Agriculture and Biological Sciences, 2023)
This article mainly describes the importance of intensive gardens today, the agrotechnics of creating gardens. At the same time, the article also describes the advantages and disadvantages of intensive gardens. Along with the formation of intensive gardens, there is also information on how to use irrigation methods.